2016
DOI: 10.1093/jme/tjw118
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Putative Male-Produced Sex Pheromone inLutzomyia cruciata(Diptera: Psychodidae), Vector ofLeishmania mexicana

Abstract: Lutzomyia cruciata (Coquillet) is a vector of cutaneous leishmaniasis in Mexico and Central America. However, several aspects of its ecology and behavior are unknown, including whether a male pheromone partially mediates the sexual behavior of this sand fly. In this study, we evaluated the behavioral response of females to male abdominal extracts in a Y-tube olfactometer. The volatile compounds from male abdominal extracts were identified by gas chromatography-mass spectrometry and compared with those of femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Papules of Lutzomyia pessoai are similar to those found in L. longipalpis and L. cruzi although they are distributed from III to VII tergal segments (Ward et al, 1993). Whereas in Lutzomyia cruciata the disseminating structures presented a mammiform appearance and they are located in IV-VII tergites (Serrano et al, 2016).…”
Section: Site Of the Sex Pheromone Production And Releasesupporting
confidence: 52%
“…Papules of Lutzomyia pessoai are similar to those found in L. longipalpis and L. cruzi although they are distributed from III to VII tergal segments (Ward et al, 1993). Whereas in Lutzomyia cruciata the disseminating structures presented a mammiform appearance and they are located in IV-VII tergites (Serrano et al, 2016).…”
Section: Site Of the Sex Pheromone Production And Releasesupporting
confidence: 52%
“…carmelinoi [ 19 ] and L . cruciata [ 20 ]. They have also been found in the closely related genus Sergentomyia , e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Evandromyia lenti and E. carmelinoi, appleshaped structures (2.7±0.1 µm in diameter x 1.6±0.1 µm in height and 2.5±0.2 µm in diameter and 1.2±0.2 µm in height respectively) with a central pore are present on the V and VI tergal segments (Spiegel et al 2002). Terpenoids including oxygenated compounds are produced in some of these other species, but they do not appear to be present in all those that have structures (Hamilton et al 2002;Hamilton et al 1999;Serrano et al 2016) and behavioural evidence for pheromonal activity for any of these compounds is lacking. SEM analysis of the tergal structures in M. migonei have revealed that they form of a shallow crater (average diameter ca.…”
Section: Introductionmentioning
confidence: 99%